?ENHANCEMENT OF BRAIN REGIONAL TRYPTOPHAN CONCENTRATION FOLLOWING ADMINISTRATION OF DIAZEPAM: A DOSE RELATED STUDY - BATOOL, FARHAT; PARVEEN, TAHIRA; HALEEM, DARAKHSHANJ (Biological Sciences - PJSIR, 1995)
Administration of diazepam at doses of 1,3 and 5 mg/kg attenuated home cage activity and open field activity of rats. Plasma concentrations of total tryptophan decreased and those of free tryptophan increased in diazepam injected rats. The concentration of tryptophan increased in the hypothalamus. striatum and cortex but not in the brain stem of diazepam injected rats. The increases in the hippocampus were only marginal and occurred at high doses of the drug. The possible mechanism for the increased availability of tryptophan to the brain and decreased serotonin turnover reported in diazepam injected rats is discussed.